The preschool child in Suka Village, North Sumatera. I. Feeding practices and measured food intake - Jane A. Kusin; H. S. R. Parlindungan Sinaga; K. Purba; U. Rengvist; J. M. Houtkooper (Paediatrica Indonesiana, 1981)
Childfeedillg practices were recorded for 398 children, age 0 - 5 years. Breastfeeding was continued for about 2 years.Supplementary food during infancy consisted mainly of rice in the form of gruels or porridge. After one year of age fish was introduced, at 2 years children were given part of the family diet composed of rice, fish and some vegetables mainly of the non-leafy type.In 2 seasons food consumption of 59 children, age 1 - 5 years was weighed. The habitual diet was somewhat low in energy (65 - 98% of RDl), ample in protein Â (108 - 158% of RDI) but inadequate in calcium (36 - 86% of RDI), iron (44 - 48% of RDI), retinol equivalents (26 - 44% 0/ RDI) and riboflavin (34 â€“ 41% of RDI).The inadequacy of the diet was mainly due to improper use of available foods, cultural habits and permissiveness of the mother towards the child. In this village nutrition and health education as well as a belter childcare can make a contribution to the diversification and improvement of the preschool child's diet.Compared with dietary intakes of preschool children on Java, the Suka diet was superior to the Javanese diet in energy and protein, similarly inferior in fat, calcium, riboflavin and retinol equivalents.